Editorial - Apivatthakakul, MD, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery Volume 42/Number 3-4 July-October 2018 is published in October 2018 along with the RCOST meeting in Pattaya. Congratulation to 3 RCOST members who get the honorary member this year including Dr. Prapan Chonyuen from Nan Hospital, Professor Dr. Keerati Charoencholvanich from Siriraj Hospital, Mahidol University and Dr. Pijaya Nagavajra from Bangkok Metropolitan Administration. This issue in your hand consists of several interesting articles. The first one is the Translation and Validation of the Thai Forgetten Joint Score for knee arthroplasty which will be one of the scoring system that translate into Thai and can be used to evaluate the outcomes in our country. The second is the development of alignment guide to facilitate the total knee arthroplasty, how to avoid the angular deformity in coronal plane. The third is the Comparison of Simultanteous Bilateral with Unilateral Total Knee Arthroplasty in Thabo Crown Prince Hospital. Bilateral TKR seems to be the aggressive procedure, however, this manuscript demonstated the results and advantages for considering one stage procedure to reduce the admission, rehabilitation and hospitalization. This can also be done in the non university hospital. Lastly, the results of tibial plating comparing the results and complications of anteromedial and anteralateral approach. This common surgery will add the point how to select the patient for both approach. There is one review article of Factors affect successful Fast-Track total knee arthroplasty. I believe you will enjoy reading them. Our journal is making progress in a positive way with supporting from the RCOST committee and all RCOST members who submit their valuable work in Orthopaedic field to demonstrated the up to date knowledge and skill or basic knowledge of Administration system to improve national policy in treating Orthopaedic patients. We will try our best aiming to have the journal list in the Level One of the Thai-Journal Citation Index (TCI) in the future.